Supplemental Material: Out-of-phase Late Pleistocene glacial maxima in the Western Alps reflect past changes in North Atlantic atmospheric circulation - Natacha Madeleine Gribenski (10790113); (281964) (2021)
Details on geomorphological and sedimentological context and luminescence dating analyses.